Factors Associated With Frailty Clinic Utilization by High‐Need High‐Risk Older Adult Veterans - Marianne Desir; Fei Tang; Carlos Gomez‐Orozco; Stuti Dang (Aging Medicine)
ABSTRACT Objectives Clinical models incorporating multidomain assessment and interventions may be helpful for older adults with frailty and other higher‐risk geriatric patients. Patient participation in these clinical programs is variable, however, and there is a need for greater understanding of the factors that influence participation. We aimed to identify patient characteristics associated with participation in an outpatient frailty clinic intervention. Methods We conducted a retrospective study of high‐need high‐risk older adult patients who were offered a frailty clinic intervention designed to assess and address their medical, functional, psychological, and social needs (FIT clinic). Consistent with the Andersen Behavioral Model of Healthcare Utilization, we identified variables in the “predisposing,” “need,” and “enabling” domains that might relate to patient participation in the clinic. Bivariate analyses were employed to explore the potential roles of the identified variables in the observed levels of patient participation. Results In the analyses of “predisposing” factors, being married and being of African American race were positively associated with FIT clinic participation (p = 0.021 and 0.036, respectively). With controlling for chronic conditions, however, African American race was no longer associated with clinic participation. In the analyses of “need” factors, patients with essential hypertension, type II diabetes mellitus, and/or overweight/obesity were more likely to attend the frailty clinic (p = 0.002, 0.012, and 0.013, respectively). There was less availability of data regarding potential “enabling” factors, and no statistically significant differences were found in the “enabling” domain. Conclusion The application of the Andersen Behavioral Model can provide insights into the participation patterns of high‐risk older Veterans in clinical interventions involving comprehensive geriatric assessments and multidomain interventions, including frailty clinics.